TINJAUAN YURIDIS TANGGUNG JAWAB HUKUM RUMAH SAKIT DALAM PENYELENGGARAAN REKAM MEDIS - Nasrin, Nasrin; Al Amin, Naufal (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This study aims to provide a clear and comprehensive overview of the procedures for maintaining medical records in accordance with applicable laws and regulations. This study is a normative juridical study using both legal and conceptual approaches. This study addresses the issue of hospital accountability in the event of errors in maintaining medical records and the provisions regarding the maintenance of medical records. Medical records are vital in the medical world, as a person's health history can be known and studied through them. The management of medical records includes the creation, maintenance, and destruction of medical record files, as regulated in the Minister of Health Regulation (Permenkes) Number 24 of 2022 concerning Medical Records